WOMEN’S DISCRIMINATION IN AMY POEHLER’S MOXIE: A FILM ANALYSIS - Nisrina, Jihan Alifah; Anggraeni, Niken (Universitas Negeri Yogyakarta, 2025)
Discrimination is found in many places. One group in particular that is affected by oppression and discrimination is women. In response to this issue, feminism has been vocal for many years. In accordance, this research uses the feminist approach to analyze the various forms of discrimination experienced by female characters in Moxie and the actions taken by them to fight this inequality. This research uses a qualitative method with descriptive analysis. The data source used comes from a film by Amy Poehler, Moxie (2021). Data were gathered by identifying instances of discrimination and the responses of female characters through screenshots and dialogues from relevant scenes. The film was viewed multiple times, and the data related to the research topic were collected and sorted before being analyzed. The analysis was conducted through a feminist lens that emphasizes gender discrimination. The results show that discrimination experienced by female students at Rockport High School occurs in various forms, namely direct discrimination, indirect discrimination, and harassment. This leads to a perception of women as weak and overlooked, exemplified by male students creating a ‘list’ that undermines women, while the school did nothing to stop it. Consequently, female characters show courage in fighting discrimination through various means, such as persuasive actions, rebellion and oration. This research has implications or raising public awareness about the importance of gender equality through media.